Winners and losers: fragmentation, trade and wages revisited - Holger Görg; Ingo Geishecker (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
Our paper investigates the link between international outsourcing and wages utilising a large household panel and combining it with industry level information on industries? outsourcing activities from input-output tables. By doing so we can arguably overcome the potential aggregation bias as well as other shortcomings that affect industry level studies. We find that outsourcing has had a marked impact on wages. Distinguishing three skill categories we find evidence that outsourcing reduced the real wage for workers in the lowest skill categories by up to 1.8% while it increased real wages for high-skilled workers by up to 3.3%. This result is robust to a number of different specifications.
Keywords: J31; L24; F16; 330; Outsourcing; Fragmentation; Skills; Wages; Lohnstruktur; Outsourcing; Internationale Arbeitsteilung; Globalisierung; Schätzung; Deutschland